2011
DOI: 10.2223/jped.2089
|View full text |Cite
|
Sign up to set email alerts
|

Non-authoritative parents and impact on drug use: the perception of adolescent children

Abstract: Objective: To evaluate the association between drug use and parenting styles perceived by Brazilian adolescent children. Methods:This cross-sectional study enrolled adolescents aged 14 to 19 years that used the Serviço Nacional de Orientações e Informações sobre a Prevenção do Uso Indevido de Drogas (VIVAVOZ). A total of 232 adolescents participated in the study. Phone interviews were conducted using the Parental Responsiveness and Demandingness Scale, which classifies maternal and paternal styles perceived by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
1
14
0
10
Order By: Relevance
“…Previous studies observed that, differently from what happens in families whose parents are indulgent or negligent, children who see their parents as authoritative and whose family relations provide support, a sense of belonging, and limits seem to accept more easily the family values and parental follow-up, and that would favor a reduced use of substances, including tobacco 13,33 . It is thus important to consider the family culture and/or the identification of the adolescent with a role model, as children are part of a family system 1,2,3 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies observed that, differently from what happens in families whose parents are indulgent or negligent, children who see their parents as authoritative and whose family relations provide support, a sense of belonging, and limits seem to accept more easily the family values and parental follow-up, and that would favor a reduced use of substances, including tobacco 13,33 . It is thus important to consider the family culture and/or the identification of the adolescent with a role model, as children are part of a family system 1,2,3 .…”
Section: Discussionmentioning
confidence: 91%
“…Many types of behavior of adolescent children are influenced by the style of their parents, including academic performance, risky sexual behavior, and the use of drugs, including tobacco 12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns autores consideram que uma pessoa pode ser capaz de tomar decisões médicas informadas antes de chegar à idade adulta, especialmente em áreas específicas como oncologia ou questões familiares (uso materno de drogas, violência doméstica) [10][11][12][13][14][15] . Shaw 16 , por exemplo, separou os menores em duas faixas etárias -16 e 17 anos e abaixo de 16 anos, e concluiu que um menor acima de 16 anos com capacidade de decisão deve ser capaz de dar consentimento competente para procedimentos médicos, mas não deve ser capaz de recusar um procedimento claramente benéfico.…”
Section: Discussionunclassified
“…Na década de 1990, Darling & Steinberg 1 propuseram um modelo teórico de parentalidade para elucidar e acomodar a relação entre estes dois complexos construtos: estilos e prá-ticas educativas parentais. Segundo a literatura específica sobre o tema, tanto os efeitos do estilo parental como os das práticas educativas parentais parecem ser extremamente importantes nos modelos que estudam o desenvolvimento e a saúde de crianças e adolescentes 3,4,5 .…”
unclassified